THE EFFECT OF GLOBALIZATION ON ROMANIAN TOURISM, DURING THE COVID-19 CRISIS - Daniela Marilena DOROBANTU; Alina MARCUTA; Cristiana TINDECHE; Maria STOIAN; Ioana NICULAE; Liviu MARCUTA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tourism, one of the branches that recorded among the largest losses during the Covid-19 pandemic, both globally and nationally, is the subject of the case study. These losses were due both to the travel restrictions imposed by each state, but also to the reluctance of tourists to travel, especially in 2020. Therefore, the number of tourists has decreased considerably, both in terms of resident tourists and tourists. non-residents. That is why in this paper we set out to analyze the ways in which the development of the Covid-19 pandemic influenced the tourist traffic, taking into account the non-resident tourists who arrived in Romania. We found that the incoming activity of tourists was well below the outgoing activity, which negatively influenced both the tourist entities and the complementary sectors, which in turn are related to the entire national economy. The research methodology consisted in collecting the existing data on the website of the National Institute of Statistics, as well as in other specialized databases, their processing, analysis and formulation of conclusions. Different research methods were used: analysis, deduction, graphical method, comparative method, as well as a series of indicators with a fixed base through which we highlighted the change in time of tourist traffic, as well as their growth rate. Based on the analyzed data, conclusions were formulated that allowed us to characterize the existing situation on the Romanian market in the period 2018-2020.